PREVENTIVE EFFORTS TO ATTACK RADICAL UNDERSTANDING THROUGH ISLAMIC EDUCATION RAHMATAN LIL ALAMIN - Maulida, Faricha Amalia; Salsabilah, Alvy Syakilah; Veranty, Eren Lukitaing; Imanda, Marshanda Nya Putri; Azahra, des; Noor, Aditia Muhammad (Academic Solution Publisher, 2024)
This article discusses understanding radical religion through Islam rahmatan lil alamin. Radical Muslims who are increasingly prevalent in Indonesia use Islam as a tool of persuasion to carry out social reforms with violence. Radicals with strong religious fanaticism often use violence to reaffirm outdated religious doctrines. For Muslims today, with the rise of radicalism in responding to terrorism, it is a serious issue. The role of educational institutions is very much needed to prevent radical Islam from countering acts of terrorism, using religion as a propaganda tool and making changes to social policies that have been planned by parties who have been involved. The author will discuss several problem formulations that have been worried by the majority of non-radical Muslims such as how to instill the teachings of Islam rahmatan lil alamain to tackle radicalism in Indonesia by using library research methods and content analysis. Content analysis is a way to study and conclude the content of the text about how to overcome radicalism in Indonesia. By writing this article the author intends to provide information about how Muslims in Indonesia deal with Muslims who adhere to the teachings of radicalism that are currently rife in Indonesia.